2020
DOI: 10.1177/1524839919881143
|View full text |Cite
|
Sign up to set email alerts
|

Community-Led Action to Reduce Menthol Cigarette Use in the African American Community

Abstract: Background. African Americans suffer a disproportionate burden of tobacco harm and researchers have posited that menthol cigarettes are a key contributor to this disparity. In 2015, a county health department and African American community-based organization (CBO) in Minnesota partnered to educate and engage the African American community on menthol and its role in tobacco-related health disparities. The following case study describes successes, challenges, and recommendations from this work. We focus on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The themes identified in this case study are consistent with previous research on local, state, and national tobacco control policies that found that, among others, policy champions or change agents [ 7 , 42 , 43 , 44 ], engagement with youth advocates [ 7 , 45 ], supporting data, and other localities previously enacting the policy influenced adoption [ 42 ]. Past studies also suggest that the absence of supporting data may have hampered states which attempted to adopt T21 early [ 6 , 7 ], but in later years, the IOM report proved powerful enough to elevate the attention of T21 as a tool to reduce youth tobacco use.…”
Section: Discussionsupporting
confidence: 84%
“…The themes identified in this case study are consistent with previous research on local, state, and national tobacco control policies that found that, among others, policy champions or change agents [ 7 , 42 , 43 , 44 ], engagement with youth advocates [ 7 , 45 ], supporting data, and other localities previously enacting the policy influenced adoption [ 42 ]. Past studies also suggest that the absence of supporting data may have hampered states which attempted to adopt T21 early [ 6 , 7 ], but in later years, the IOM report proved powerful enough to elevate the attention of T21 as a tool to reduce youth tobacco use.…”
Section: Discussionsupporting
confidence: 84%
“…Our review highlights the need for a comprehensive study of the association between policy mechanisms (e.g., policy provisions, exemptions, implementation actions, and challenges) and outcomes, which could provide evidence-based guidance for improving policy development and implementation, 51 , 52 especially to address endemic health inequities associated with target marketing of flavored and menthol tobacco products. 8 , 53 , 54 Indeed, few studies have specifically assessed the health equity impacts of sales restrictions among population groups who disproportionately suffer from tobacco-related disease and death, such as Black Americans. 55 Recent studies that have investigated health equity impacts of flavored and menthol sales restrictions reveal, for example, that: (a) the rationale for menthol tobacco sales restrictions was not well-understood or universally supported by African American smokers in Minneapolis and St. Paul, MN 56 ; (b) compared to White, non-Hispanic youth, Black, Hispanic, Asian, and LGBTQ youth in various California localities with flavor policies reported greater difficulty in accessing policy-restricted flavored tobacco products 57 ; and (c) Black young adults in San Francisco were more likely than other young adults to continue using flavored cigars after implementation of the flavored and menthol sales restriction in that city.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar publication has discussed how a menthol cigarette ban can protect African American communities [ 32 ]. In the real world, many community-based organizations in African American communities were also taking action to educate members of their communities about the risks of smoking menthol cigarettes and engaging community members to reduce the use of menthol cigarette [ 33 ]. The proposed menthol cigarette rules will further support community-based organizations’ efforts in reducing menthol cigarette smoking among African Americans.…”
Section: Discussionmentioning
confidence: 99%